Activation of p38 and changes in mitochondria accompany autophagy to premature senescence-like phenotype switch upon chronic exposure to selenite in colon fibroblasts - Rudolf, Emil; Rezáčová, Kateřina; Cervinka, Miroslav (Toxicology letters, 2014)
Effects of chronic exposure to supranutritional sodium selenite (Se) were investigated in colonic fibroblasts. Initially, Se did not produce any gross changes in exposed cells; however, basal levels of autophagy were transiently increased and p38 activity was stimulated. From the 3rd week onwards, Se decreased cell proliferation, with corrensponding changes in cell cycle distribution. Also, in exposed cells oxidative stress and DNA damage slowly but gradually increased along with decreasing mitochondrial function and upon continued elevated activity of p38 kinase. Towards the end of the experiment, premature senescence features became more prominent in treated cells. Pharmacological inhibition as well as gene knockdown of these processes confirmed the involvement of p38 in balancing autophagy and premature senescence in cells exposed to Se and suggests that this element may in a given time frame compromise selected cell populations in digestive system.
Keywords: aktivace enzymů; kolon; p38 Mitogen-Activated Protein Kinases; proliferace buněk; DNA Damage; Phenotype; buněčné linie; Autophagy; oxidační stres; seleničitan sodný; Mitochondria; Enzyme Activation; Fibroblasts; Cell Cycle; Oxidative Stress; transfekce; Time Factors; časové faktory; Colon; Transfection; lidé; Sodium Selenite; p38; stárnutí buněk; Premature senescence; replikace DNA; signální transdukce; fibroblasty; metylace DNA; Signal Transduction; mitogenem aktivované proteinkinasy p38; Cell Line; buněčný cyklus; mitochondrie; autofagie; Sodium selenite; Colonic fibroblasts; poškození DNA; DNA Methylation; Cell Proliferation; fenotyp; DNA Replication; Cellular Senescence; Humans